Perianal streptococcal dermatitis and guttate psoriasis. Case report. - Romano, I.; Venturi, C.; Bassissi, P. (European Journal of Pediatric Dermatology, 2002)
A case of perianal streptococcal dermatitis associated with guttate psoriasis is described in a 12-year-old boy. Possible pathogenetic correlations between the two disorders emphasize the necessity to examine pediatric patients with guttate psoriasis and to swab the pharynx, perianal and/or perigenital areas to search bacterial infections.